Activity-based profiling for drug discovery - Serwa,R; Tate,EW (Chemistry and Biology, 2011)
Activity-based protein profiling (ABPP) is emerging as a game-changing tool for drug discovery, target validation, and basic biology. In this issue, Chang et al. (2011) report the ABPP-facilitated discovery of JW480, a highly selective potent and orally bioavailable inhibitor of monoalkylglycerol ether hydrolase KIAA1363 that dramatically impairs in vivo growth of human prostate cancer cell lines.